Effects of Supraphysiologic Levels of Estradiol on Endometrial Decidualization, sFlt1, and HOXA10 Expression. (December 2019) - Cottrell, Hanh N.; Deepak, Venkataraman; Spencer, Jessica B.; Sidell, Neil; Rajakumar, Augustine
Objective: Supraphysiologic estradiol (E2 ) levels associated with controlled ovarian hyperstimulation in high in vitro fertilization (IVF) responders may alter implantation and placentation and increase the risk of preeclampsia. Our hypothesis is that elevated E2 levels in vitro significantly alter endometrial decidualization, sFlt1, and HOXA10 expression. Methods: Human endometrial stromal cells were treated with a decidualization cocktail of medroxyprogesterone, cyclic adenosine monophosphate, and 3 concentrations of E2 10 nM (standard), 100 nM (intermediate), or 1000 nM E2 (high). Effects on sFlt1, prolactin (PRL), insulin-like growth factor binding protein 1 (IGFBP-1), vascular endothelial growth factor (VEGF), and HOXA10 were studied. Results: Prolactin, IGFBP-1, and VEGF significantly increased at all 3 E2 concentrations. While IGFBP-1 and VEGF did not change with increasing E2, PRL was less with high E2 (6.0 ng/mL ± 1.4 standard error of the mean) compared to standard (21.4 ± 3.2) and intermediate (19.8 ± 3.8). sFlt1 decrease was similar at all E2 concentrations. HOXA10 was lower at standard (10%) and intermediate (30%) as expected, but did not change with high E2 . Conclusions: Supraphysiologic E2 levels associated with high IVF responders that exceed in vivo levels may impair in vitro endometrial decidualization. Although PRL did increase with high E2, the levels were, however, attenuated and 3.4-fold lower than standard and intermediate E2 . sFlt1 was decreased under all 3 conditions with no differences between concentrations. Reduced HOXA10 was not observed with high E2 . These findings suggest that elevated E2 levels in vitro may alter endometrial decidualization and subsequently affect implantation and placentation.